Best Answer

There are two terms in that expression. They are " 9h " and " 13 ".

Q: What are the terms in the expression 9h plus 13?

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

9h + 2 < - 79 9h < - 81 h < - 9

-98-4h+8k-40+k-9h = (-98-40)+(-4h-9h)+(8k+k) = -138-13h+9k

-9h-6+12h+40=22 -9h+12h=22-40+6 3h=-12 h=-4

-9h - 6 + 12h + 40 = 22, simplifying this gives12h - 9h + 40 - 6 = 223h + 34 = 22, taking 34 off both sides gives3h + 34 - 34 = 22 - 343h = -12, thush = -12/3 = -4

The answer to 9h + 2 < -79 is H < -9

Related questions

-9h-6+12h+40=22

That's not an equation, and there's no solution required.An equation has an 'equals' sign ( " = " ) somewhere in it.That expression is just 9h - 77. Its numerical value depends on what 'h' is. Every time'h' changes, the value of that expression changes. That's all there is to say about it.

9h^2+24h+16=(9h+16)(h+1)

9h + 2 < - 79 9h < - 81 h < - 9

9h + 2 = -79 9h = -81 h = -81/9 h = -9

-98-4h+8k-40+k-9h = (-98-40)+(-4h-9h)+(8k+k) = -138-13h+9k

h-9h-6+12h+40 = 22 h-9h+12h = 22+6-40 4h = -12 h = -3

5h - 3h + 9h = 176 11h = 176 h = 16

h <9

It is: 9h+4(2+h) = 9h+8+4h => 13h+8

-9h-6+12h+40=22 -9h+12h=22-40+6 3h=-12 h=-4

-9h-6+12h+40 = 22 3h+34 = 22 3h = 22-34 3h = -12 h = -4